PROFESSORS' PERCEPTION OF SCIENTIFIC ACTIVITY IN THE FACULTY OF MEDICAL SCIENCES OF THE UNIVERSITY OF GUAYAQUIL - Nader, Jorge Daher; Panunzio, Amelia Patricia; Navarro, Marlene Hernández (International Journal of Research -GRANTHAALAYAH, 2020)
Research is considered a function aimed at obtaining new knowledge and its application for the solution to problems or questions of a scientific nature, The universities framed in the fulfillment of their social function have a complex task given by training a competent professional who assumes research as part of their training and who learns to ask questions that they are able to solve through scientific research. Scientific research is an indicator of the quality of processes in the university environment, so it must be increased by virtue of the results of the work carried out by research teachers and students the objective of this work is to know the perception of the teachers of the Faculty of Medical Sciences of the University of Guayaquil about the scientific activity. Objective: to know the perception of the teachers of the Faculty of Medical Sciences of the University of Guayaquil about the scientific activity. Methods: theoretical and empirical level were used, a questionnaire with closed questions aimed at knowing the opinions on the research activity in this institution was applied. Result: that of the sample analyzed 309 (39.3%) said they agreed with the training for the writing of scientific articles. 38.6% said they agree with the training on research projects. Conclusion: that teacher’s research should be enhanced to ensure the formation and development of research skills in students.